Integrating Scratch with Project-Based Learning to Cultivate Students' Academic Performance - Wenny Pinta Litna Tarigan; Paidi Paidi; Antuni Wiyarsi; Suhartini Suhartini; Sukma Fajri (Yayasan Keluarga Guru Mandiri, 2024)
This study addresses the challenge of enhancing students' academic performance, including creativity, learning achievement, problem-solving ability, motivation, and attitude, by integrating problem-solving into biology lessons through Scratch and Project-based Learning (PjBL). The focus was on high school students studying the digestive system, a topic often taught through traditional lecture-based methods, which can limit engagement and deeper understanding. A quasi-experimental design with a nonequivalent control group pretest-posttest was employed, involving 105 eleventh-grade students divided into three groups: PjBL with Scratch, PjBL without Scratch, and a control group receiving direct instruction (DI). The same teacher taught all groups to ensure consistency. Research instruments included cognitive tests, problem-solving assessments, and questionnaires measuring creativity, motivation, and attitudes toward biology and programming. Results indicated that PjBL with the Scratch group significantly outperformed the other two groups in all aspects, demonstrating improved learning outcomes and a greater ability to apply knowledge in creative and meaningful ways. Students expressed higher motivation and more positive attitudes toward the subject matter. This study concludes that integrating Scratch with PjBL enriches biology education and enhances interdisciplinary learning. The findings contribute to educational science by offering a scalable, innovative model that bridges STEM fields and fosters critical 21st-century skills.